Isolation gowns as a potential work hazard. Issue 6 (6th May 2020) - Schirmer, Abigail; Sessions, Renard; Gravenstein, Nikolaus; Rand, Kenneth; Oli, Monika; Cooper, Lou Ann; Sappenfield, Joshua W
Abstract: Objectives: Isolation gowns are used as a barrier to bacterial transmission from patient to provider and vice versa. If an isolation gown is ineffective, the patient and provider have a potential breach of safety and increased infection risk. This study compared the bacterial permeability of differently rated, commonly uses isolation gowns to assess their effectiveness in preventing simulated bacterial transmittance, and thus contamination, from patient to provider. Methods: Serial dilutions of Staphylococcus epidermidis in sterile saline were applied to a simulated skin surface. Unrated and Levels 1 through 4 non-sterile isolation gowns contacted the solution, simulating patient contact. Both sides of the contaminated gowns were then cultured on blood agar by rolling a sterile swab across the gown and evenly inoculating the culture plate. Colony counts from inside and outside of the gowns were compared. Separately, S. epidermidis was placed on a sample of each gown and scanning electron microscopy was used to visualize the contaminated gowns' physical structure. Results: Mean bacterial transmittance from outside of the gown (i.e. patient contact side) to inside of the gowns (i.e. provider clothing or skin side) based on gown rating was as follows: unrated: 50.4% (SD 9.0%); Level 1: 39.7% (SD 11.2%); Level 2: 16.3% (SD 10.3%); Level 3: 0.3% (SD 0.8%); Level 4: 0.0% (SD 0.0%). Scanning electron microscope imaging of unrated, Level 1, and Level 2 gowns revealed gown pore sizes much larger than the bacteria. The Welch one-way analysis of variance statistic showed significant difference dependent on gown-level rating. Conclusions: Unrated, Level 1, and Level 2 isolation gowns do not provide effective bacterial isolation barriers when bacteria like S. epidermidis make contact with one side of the gown material. Not studied, but implied, is that unrated and lower rated isolation gowns would be as or even more physically permeable to virus particles, which are much smaller than bacteria.